A SINGULAR INTERVAL RECONSTRUCTION LOCAL MEAN DECOMPOSITION AND ITS APPLICATION IN BEARING FAULT DIAGNOSIS OF RECIPROCATING COMPRESSOR (MT) - ZHAO HaiYang; LI Xue; LIU ZuJian; WANG JinDong; FENG Shuai (Jixie qiangdu)
Aiming at the mutation in demodulation of the envelope estimation function, a local mean decomposition method for singular interval envelope reconstruction is proposed. This method determines that the reason for the sudden change in the demodulation of the envelope estimation function is the intersection of the envelopes, and defines the local area where the intersection exists as a singular interval. Combined with the extreme value symmetry theory, the interpolation points in this interval are expanded, and the cubic Hermitian interpolation is used to perform local reconstruction. A singular interval envelope reconstruction algorithm is formed. The simulation signal and the application of fault diagnosis of reciprocating compressor bearing prove that the proposed method solves the envelope crossing problem, suppresses the demodulation mutation phenomenon, and the decomposition result has more obvious fault characteristics.